Aspectos epidemiológicos de pacientes con trauma torácico en el Hospital Regional Docente de Trujillo, Perú. 2010 - 2014 - Vásquez López, Luis Felipe (2017)
Epidemiology of patients with thoracic trauma was determined at the “Hospital Regional Docente de Trujillo”, Peru from January 2010 to December 2014. A retrospective, descriptive study was carried out to analyze 312 clinical histories of patients with a diagnosis of thoracic trauma in an emergency at the “Hospital Regional Docente de Trujillo”, from January 2010 to December 2014, excluding incomplete clinical histories. Age, sex, etiology and type of thoracic trauma were recorded. There were 255 (81.73%) men and 57 (18.27%) women, the most frequent age group was between 21 and 30 years old, with 73 cases (23.4%), mean age was 37.1 ± 17.39 years. The most frequent etiology was traffic accident in 89 patients (28.53%). The type of thoracic trauma was penetrating 166 (53.21%) patients and closed 146 (46.79%) patients. The type of closed thoracic trauma, caused by blow in 79 cases (54.11%) and penetrating, by projectile of firearm in 119 cases (71.69%). Thoracic trauma is more frequent in male adults aged 21-30 years, caused by traffic accidents and the most frequent type of thoracic trauma is the penetrating by projectile of firearm